Application of an atmospheric dielectric barrier discharge for inactivation of bacteria - Chin, Oi Hoong; Lai, K.L.; Thong, Kwai Lin; Wong, Chiow San (Akademi Sains Malaysia & Confederation of Scientific & Technological Association in Malaysia (COSTAM), 2014)
An atmospheric pressure dielectric barrier discharge (DBD) system capable of operating under both positively biased voltage pulses at 500 Hz and sinusoidal AC voltage at 8.5 kHz was constructed. The 500 Hz operation produced DBD plasma that was visually more uniform, whilst optical emission from DBD at 8.5 kHz operation was more intense. Though the inactivation of Gram-positive bacteria, Bacillus cereus took longer time than the Gram-negative bacteria, Escherichia coli ATCC 25922 and Salmonella enteritidis, complete sterilization was generally achieved in about 1 minute of DBD plasma treatment.